EFEKTIVITAS BIMBINGAN KELOMPOK DENGAN TEKNIK DISKUSI UNTUK MENINGKATKAN RASA PERCAYA DIRI SISWA KELAS X TATA BUSANA SMK NEGERI 5 KOTA PONTIANAK - Rischa Dwi Rahmawati; Muhammad Asrori; Luhur Wicaksono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to test the effectiveness of group guidance services using discussion techniques to increase student self-confidence at SMK Negeri 5, Pontianak City. This study used an experimental method with a pre-experimental design and a one-group pretest-posttest design. The data collection technique used was a self-confidence inventory. Data analysis used a parametric paired sample t-test. The results showed that students' pre-test scores had an average percentage of 37.5%, categorized as low, and post-test scores had an average percentage of 79.375%, categorized as high, an increase of 31.88%. The results of the hypothesis test showed a t-value of 7.716 with a significance value of 0.000 <0.05, which means H0 is rejected and Ha is accepted. Thus, it can be interpreted that there was a significant increase after being given group guidance with discussion techniques to increase student self-confidence at SMK Negeri 5, Pontianak City